Cooling System Performance Comparison of Refrigerant R-134a and MC-134 on Ice Slush Machine - Rizki Muliawan; Azel Adnal A; Tandi Sutandi; Nurrohman Nurrohman (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2021)
Ice Slush Machine uses a direct cooling vapor compression system. The primary refrigerant used in such a system mostly is hydrofluorocarbons (HFCs), such as R134a. R134a is a retrofit for refrigerant R-12 which is included in the chlorofluorocarbon (CFC) type of refrigerant. CFC-type refrigerants have a dangerous impact on the environment. Hydrocarbon refrigerant MC-134 is an alternative for R-134a because it has a low potential value for environmental damage. The secondary refrigerant used was propylene glycol and the product used was 3.5 liters of Coca-Cola. From the test results when the system using R134a had an average COPactual and an average COPcarnot of 2.6 and 4.55, respectively, and the energy consumption was 1.571 kWh with an average efficiency of 57%, while in a system with MC-hydrocarbon refrigerant 134 obtained an average COPactual and an average COPcarnot of 2.8 and 4.5, respectively and the energy consumption of 1.325 kWh with an average efficiency of 62%. Therefore, MC-134a had COP actual greater than R-134 and electrical energy consumption of MC-134 was less than R-134a.